THE INFLUENCE OF GREEN MARKETING AND BRAND IMAGE ON CONSUMER LOYALTY IN SUPPORTING THE ACHIEVEMENT OF SDGS IN THE RETAIL INDUSTRY - Dindin Aminudin; Abu Naim; Fachmi Al Faroqi; Ikraman; Nor Fatah Ulinnuha; Danu Noval Ramadhoni (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Awareness of environmental issues is driving the retail industry to adopt green marketing strategies as an effort to support the Sustainable Development Goals (SDGs). However, there are still issues regarding low consumer loyalty amidst intense competition and sustainability demands. This research aims to analyze the influence of green marketing and brand image on consumer loyalty in the context of achieving SDGs, specifically in the retail industry of Tangerang Regency.This research uses a quantitative approach with 200 respondents selected thru purposive sampling. Data was collected thru Likert-scale questionnaires and analyzed using multiple linear regression via SPSS. The analysis results show that green marketing has a significant positive effect on consumer loyalty with a coefficient of 0.412 and a significance value of 0.000 (p < 0.05), contributing 41.2% of the influence. Brand image also has a significant positive effect with a coefficient of 0.368 and a significance value of 0.000 (p < 0.05), contributing 36.8%. Simultaneously, both variables explain 62.5% of the variation in consumer loyalty (R² = 0.625). This finding indicates that consistent implementation of green marketing and building a brand image aligned with sustainability values can significantly increase consumer loyalty and support the achievement of SDGs in the retail sector.